2022
DOI: 10.1101/2022.01.18.22269420
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Immune response to third SARS-CoV-2 vaccination in seronegative kidney transplant recipients: possible improvement by mycophenolate mofetil reduction

Abstract: Background: Modification of vaccination strategies is needed to improve the immune response to SARS-CoV-2 vaccination in kidney transplant recipients (KTRs). Methods: This multicenter observational study aimed to determine antibody kinetics among 60 seropositive KTRs and analyzed the effects of the third vaccination against SARS-CoV-2 in 174 previously seronegative KTRs. We investigated whether mycophenolate mofetil (MMF) dose reduction by 25-50% prior the third vaccination influences vaccination success. … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 28 publications
0
5
1
Order By: Relevance
“…Loss of antibodies at 2 months and 4 months after vaccination occurred in a substantial number of initially responding individuals, presumably resulting in a loss of protection against COVID-19. While it is known that patient receiving MPA have a low vaccination response rate (14,17), our results suggest that use of MPA is also associated with a delay in vaccination response resulting in increasing Ig levels over time in almost 18% of patients. Most importantly, we noted a high variability in the development of humoral protection over time between KTR.…”
Section: Discussioncontrasting
confidence: 53%
“…Loss of antibodies at 2 months and 4 months after vaccination occurred in a substantial number of initially responding individuals, presumably resulting in a loss of protection against COVID-19. While it is known that patient receiving MPA have a low vaccination response rate (14,17), our results suggest that use of MPA is also associated with a delay in vaccination response resulting in increasing Ig levels over time in almost 18% of patients. Most importantly, we noted a high variability in the development of humoral protection over time between KTR.…”
Section: Discussioncontrasting
confidence: 53%
“…Loss of antibodies at 2 and 4 months after vaccination occurred in a substantial number of initially responding individuals, presumably resulting in a loss of protection against COVID-19. While it is known that patients receiving MPA have a low vaccination response rate [ 17 , 21 ], our results suggest that the use of MPA is also associated with a delay in vaccination response, resulting in increasing Ig levels over time in almost 18% of patients. Most importantly, we noted a high variability in the development of humoral protection over time between KTR.…”
Section: Discussionmentioning
confidence: 56%
“…A few studies have examined the effect of MPA withdrawal to enhance vaccination responsiveness in small cohorts ( 55 , 56 ). After showing a dose-dependent effect of MPA on antibody levels after two COVID-19 vaccinations, Kantauskaite et al examined the effect of temporary MPA dose reduction by 25–50% in 24 KTR receiving a third mRNA vaccination matched to 24 KTR without changes in immunosuppressive maintenance therapy ( 31 , 55 ).…”
Section: Discussionmentioning
confidence: 99%
“…A few studies have examined the effect of MPA withdrawal to enhance vaccination responsiveness in small cohorts ( 55 , 56 ). After showing a dose-dependent effect of MPA on antibody levels after two COVID-19 vaccinations, Kantauskaite et al examined the effect of temporary MPA dose reduction by 25–50% in 24 KTR receiving a third mRNA vaccination matched to 24 KTR without changes in immunosuppressive maintenance therapy ( 31 , 55 ). The authors found significantly higher antibody levels in patients with MPA reduction 3 weeks prior until 1 week after third vaccination, however, patients were not followed-up on graft function or development of DSA ( 55 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation